Penggunaan Teknik Desentralisasi Sistematis Dalam Manajemen Stres Mahasiswa Program Studi Bimbingan dan Konseling Universitas Sultan Ageng Tirtayasa - Raudah Zaimah Dalimunthe; Rahmawati Rahmawati (Universitas Sultan Ageng Tirtayasa, 2019)
Abstract Systematic decentralization is a technique to reduce emotional response by using relaxation methods. Decentralization techniques serve to reduce stress pressure experienced by individuals. The purpose of this study was to find out the use of systematic decentralization techniques in the management of stresses. The method in this study is qualitative descriptive, survey, and literature study. The research sample was 6th semester students of 2017/2018 Academic Year in Guidance and Counseling Study Program FKIP Sultan Ageng Tirtayasa University. The stages of implementing a relaxation treatment of decentralization techniques can be carried out, as follows: first stage, second stage and third stage. The results of the study show that systematic decentralization techniques can be used in managing stress in students. This can be seen from the results of interview analysis to students given relaxation treatment students with systematic decentralization techniques. Keyword: Systematic decentralization, stress management